FEATURES OF THE PROTECTION OF THE RAILWAY AND TERRITORIES IN MOUNTAIN AND STEPPE REGIONS OF UZBEKISTAN - Abdazimov Shavkat Khakimovich; Yuldasheva Nargiza Patkhullaevna (Scholar Express Journal, 2023)
The most common natural hazards in mountainous areas are earthquakes, mudflows, landslides, landslides, and snow avalanches. For the steppe regions, hurricanes, storms and tornadoes, snow drifts are most characteristic
Keywords: earthquakes; mudflows; landslides; natural hazards in mountainous